Radiocarbon chronology of the Neolithic-Eneolithic period in the Karelian Republic (Russia) - Tarasov, Alexey Yur'evich; Nordqvist, Kerkko; Mökkönen, Teemu; Khoroshun, Tatyana (Documenta Praehistorica, 2017)
This article discusses a radiocarbon-based chronology for the Neolithic–Eneolithic period in the present-day Republic of Karelia (Russian Federation). The main goal is to present all currently available radiocarbon datings, including the previously published dates, as well as the ones recently obtained by the authors. In total, there are 194 dates from 77 sites covering the period from the 6th to the 2nd millennium cal BC. Besides providing an up-to-date list of datings, the article also evaluates their reliability and utility in building a local chronology. Despite several shortcomings, the new AMS-supported chronology enables the study of past cultural dynamics in much greater detail than previously and allows its better integration into the wider north-east European chronological framework. V članku razpravljamo o radiokarbonski kronologiji obdobij neolitika-eneolitika v današnji Republiki Kareliji (Ruska federacija). Predstaviti želimo vse razpoložljive datume, tako tiste že objavljene kot tudi najnovejše datume, ki smo jih pridobili avtorji. Skupno je sedaj na voljo 194 datumov iz 77 najdišč, ki pokrivajo čas od 6. do 2. tisočletja pr. n. št. Poleg novega seznama vseh radiokarbonskih datumov ocenjujemo v članku tudi zanesljivost in koristnost le-teh za oblikovanje lokalne kronologije. Kljub številnim pomanjkljivostim omogoča nova kronologija, ki temelji na AMS radiokarbonskih datumih, veliko bolj natančne študije preteklih kulturnih dinamik, kot je bilo to možno v preteklosti, ter omogoča boljšo integracijo v kronološke okvirje na širšem območju severovzhodne Evrope.